D'Nimbe Sdn Bhd : wireless weighing scales and braided cable / Muhammad Firdaus Md Khider ... [et al.] - Muhammad Firdaus, Md Khider; Muhammad Aiman, Nor Azman; 'A Yuni Nadhirah, Mohamad Yamin; Nur Aina Ida Yu, Mohd Suhaimi; Nur Hanim Syafiqa, Shamsul Kamal; Wan Nor Hafizah, Wan Ahmad Saifuddin (2019)
D'Nimbe Sdn. Bhd is a company that focus on selling a multifunction weighing scales for customers and provides a braided cable weighing scale to reduce the risk of the cable to bend or cut that can cause harm to people. Other than that, for the multifunction weighing scale, we provide battery as the main source and solar energy as a backup. Tanah Merah is an area that many people get into business such as open up a shop, fishmongers and supermarket, hence it causes demand of weighing scale as many people get into business rise over the year. While there are currently three businesses like us in Tanah Merah, however our business have our own speciality such as delivery services and multifunction weighing scale. D'Nimbe Sdn. Bhd. marketing strategy is to emphasize the quality and price of our products and services. We offer an affordable price because some people in Kelantan has a very low income and poor family. Thus, we develop marketing strategy that gives attraction to come to our shop. The management of D'Nimbe Sdn. Bhd. consists of 6 workers which is Muhammad Firdaus, Wan Nor Hafizah, 'Ayuni Nadhirah, Muhammad Aiman, Nur Aina ldayu and Nur Hanim Syafiqa. Our workers has extensive experience in finance, businesses, sales and accounting and we will be taking this responsibilities together instead of different duties and portfolio of partners. Besides, we have service and products commitments plan to promote and distribute our product through newspaper, media social and signboard as a platform. So we hopes that our business can grow and compete with other businesses in Malaysia.